Cognitive Functioning Self-Assessment Scale (CFSS): Further psychometric data. Issue 1 (2nd January 2018) - Annunziata, Maria Antonietta; Muzzatti, Barbara; Flaiban, Cristiana; Giovannini, Lorena; Lucchini, Guido
ABSTRACT: The "Cognitive Functioning Self-Assessment Scale" (CFSS) is a questionnaire specifically developed for the self-reporting of cognitive functioning in non-neurologic settings. A previous published study had showed its good reading comprehension and face validity, defining it as monofactorial and reliable. This paper provides further psychometric data and norms derived on a larger sample from the general population. Our work is divided into two studies. In Study 1, 194 adult patients in a General Practitioner study (27.8% retested after 2 weeks) have filled-in the CFSS together with the CES-D, the State Anxiety subscale of the STAI, and a clinical and socio-demographic data form. The Cronbach's alpha of the CFSS was 0.878; the temporal stability was 0.794; in addition, CFSS showed substantial and moderate associations respectively with depression and state anxiety measures. In Study 2, CFSS data on 476 participants have been considered. CFSS score was associated to age ( p  < 0.01) and education ( p  < 0.01). In addition, CFSS descriptive statistics according to age and education levels were provided. In conclusion, although further research is surely necessary to refine the CFSS, the herein presented data together with the already published results, confirm the validity and reliability of this tool.